A TNF-like trimeric lectin domain from Burkholderia cenocepacia with specificity for fucosylated human histo-blood group antigens - Šulák, Ondřej; Cioci, Gianluca; Delia, Monia; Lahmann, Martina; Varrot, Annabelle; Imberty, Anne; Wimmerová, Michaela (Structure, 2010)
The opportunistic pathogen Burkholderia cenocepacia expresses several soluble lectins, among them BC2L-C. This lectin exhibits two domains: a C-terminal domain with high sequence similarity to the recently described calcium-dependent mannose-binding lectin BC2L-A, and an N-terminal domain of 156 amino acids without similarity to any known protein. The recombinant N-terminal BC2L-C domain is a new lectin with specificity for fucosylated human histo-blood group epitopes H-type 1, Lewis b, and Lewis Y, as determined by glycan array and isothermal titration calorimetry. Methylselenofucoside was used as ligand to solve the crystal structure of the N-terminal BC2L-C domain. Additional molecular modeling studies rationalized the preference for Lewis epitopes. The structure reveals a trimeric jellyroll arrangement with striking similarity to TNF-like proteins, and to BclA, the spore protein from Bacillus anthracis which may play an important role in bioadhesion of anthrax spores in human lungs.
Keywords: Epitopes; vazebná místa; Fucose; Protein Structure, Quaternary; sekvence aminokyselin; bakteriální proteiny; Lectins; Bacterial Proteins; lidé; Molecular Sequence Data; antigeny krevních skupin; Amino Acid Sequence; lektiny; Models, Molecular; fukosa; molekulární sekvence - údaje; molekulární modely; Sequence Alignment; Blood Group Antigens; kvarterní struktura proteinů; epitopy; sekvenční seřazení; Burkholderia; Binding Sites; Humans